The Role of Family Literacy in Developing Children's Reading Interests in Kindergarten and the First Three Classes - Sa`di, Imad; Mansi, Etaf (Jordan Journal of Educational Sciences, 2011)
This study aimed at exploring the role of family literacy in the development of reading interests of children in light of some variables. The sample of the study consisted of 746 kindergarten and elementary schoolchildren, studying in public schools at Irbid First Directorate of Education and their parents. Family Literacy Scale consisting of 48 items and Reading Interest Scale consisting of 30 items were developed and utilized to achieve the study purposes. The results revealed a moderate level of the role of family literacy in developing children's reading interests. Parent's beliefs about reading ranked first, followed by instruments (tools), whereas activities came third, and home-school connection fourth. Although the results revealed a low degree of reading interests, statistically significant differences in reading interests due to the child study level were found in favor of the first three classes, whereas no statistically significant differences due to either child gender or the interaction between child gender and study level were found. Results also revealed significant positive correlation between all family literacy domains and domains of "instruments, activities, parent's beliefs about reading, home-school connection and fathers' and mothers' educational level, family income, family size and child's study level" with reading interests, in addition to a relative significant contribution of "activities, child's study level, tools, parents' educational level, family size, home-school connection" in predicting reading interest.